Pengaruh Media Gambar terhadap Prestasi Belajar Siswa Subtema 2 Pertumbuhan dan Perkembangan Manusia Kelas III SD Negeri 091522 Marubun Jaya - Mariajoya F. R. Panjaitan; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
This study aims to determine the effect of picture media on student achievement in the sub-thema 2 class III in SD Negeri 091522 Marubun Jaya. This study held in SD Negeri 091522 Marubun Jaya in august 2022. This research used is quantitative research using Quasi Eksperimental Design type Nonequivalent Control Group Design With the sample in the study is class students III A and III B as much 50 student. The variables in this study are picture media (x) and learning achievement (y). Methods of collecting data using tests. The data analysis technique used the normality test, homogeneity test, and hypothesis testing. based on the results of research that has been carried out for image media test data with a sample of 50 students, then the experimental class posttest scores with an average value of 43.20. posttest experimental class with an average value of 80.80. control class posttest with an average value of 40.00. control class posttest with an average value of 70.80.